The Effect of Clothing as an Intermediate Target on Dispersion of Shotgun Pattern on the Body - Üner, Hüseyin Bülent; Şam, Bülent; Kurtaş, Ömer; Atasoy, Cüneyt (The Bulletin of Legal Medicine, 1997)
From the area of scattered pellets, a rough estimation of range can be made. If a shot is fired in close range and pellets hit the clothing en masse this intermediate target will cause an increase in the dispersion of the shot. This ricochet phenomenon has been termed the “billiard ball ricochet effect”. The thickness of the clothing, the nature of the fabric and the number of layers of the garment can alter this dispersion of the shot. In the case we present, although the pellets hit the clothing en masse, the size of shot pattern on the body was over a large area. Key words: Shotgun, ricochet effects, intermediate targets, clothing, ballistics.